Implementation of the Loving Mother Movement (GSI) Program in an Effort to Reduce Maternal Mortality Rates - Parhusip, Nenny Aurelia; Ika Nursaputri; Luci Riani Br. Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: The Gerakan Sayang Ibu (GSI) is a movement implemented by the community in collaboration with the government to improve the quality of life for women, particularly by accelerating the reduction of maternal mortality during pregnancy, childbirth, and postpartum (Manuaba, 2019).Objectives: The study aims to explore the implementation of the Community-Based Sanitation Program’s first pillar in Sipahutar Subdistrict, North Tapanuli Regency. Research method: This research is a qualitative study with a descriptive approach. Results The results of this study indicate that the communication and dissemination of policy information from policymakers to policy implementers are carried out in a structured manner. Conclusion: Based on the research conducted in Sipahutar Subdistrict, it can be concluded that the implementation of the Gerakan Sayang Ibu program is structured, supported by adequate facilities, village funds, and clear Standard Operating Procedures (SOPs). However, the main challenges include a lack of human resources, low participation of pregnant women due to difficult access, limited family education, and insufficient health budgets. Despite these challenges, cross-sectoral coordination demonstrates a strong commitment to reducing maternal and newborn mortality risks.